2017
DOI: 10.1021/acs.jpcc.6b11474
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tunneling Electron Injection on the Dynamic Motion of Confined Molecules in Self-Assembled Molecular Corrals

Abstract: The dynamic motion of trimethylphosphine (TMP) adsorbates enclosed in self-assembled pyrrole molecular corral structures was observed using scanning tunneling microscopy (STM) techniques. Sequential STM images were obtained under various sample bias and tunneling current conditions to investigate the influence of tunneling conditions on the TMP dynamic motion. It was observed that the TMP adsorbates attempt to move more frequently at lower sample bias conditions, and the TMP movement holds a linear-like relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…It has observed that the trimethylphosphine (TMP) molecules adsorbed on a corner-adatom position of Si(111) -(7×7) reconstructed surface move dynamically inside self-assembled pyrrole molecular fences due to the mutual repulsive force exerted by the TMP adsorbates [5], [6]. Further studies on the molecular system confirm that this dynamic movement also affected by various tunneling electron injection conditions, especially sample bias voltage because of the influence of the antibonding orbitals of the Si-P bond [7]. We suggest that an electric field can be formed if there is an excess amount of positive ions due to high P doing and this electric field can affect the dynamic movement of adsorbed molecules on the substrate surface.…”
Section: Introductionmentioning
confidence: 95%
“…It has observed that the trimethylphosphine (TMP) molecules adsorbed on a corner-adatom position of Si(111) -(7×7) reconstructed surface move dynamically inside self-assembled pyrrole molecular fences due to the mutual repulsive force exerted by the TMP adsorbates [5], [6]. Further studies on the molecular system confirm that this dynamic movement also affected by various tunneling electron injection conditions, especially sample bias voltage because of the influence of the antibonding orbitals of the Si-P bond [7]. We suggest that an electric field can be formed if there is an excess amount of positive ions due to high P doing and this electric field can affect the dynamic movement of adsorbed molecules on the substrate surface.…”
Section: Introductionmentioning
confidence: 95%